2020
DOI: 10.1159/000504245
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Composition and Intradialytic Hypotension in Hemodialysis Patients

Abstract: Background/Aim: The relationship between body mass index (BMI) and intradialytic hypotension (IDH) has been inconsistently reported, but no further research has investigated the correlation between body composition and IDH so far. This study aimed to determine whether the lean tissue index (LTI), fat tissue index (FTI), or both derived from body composition monitoring (BCM) is associated with IDH defined as a nadir intradialytic systolic blood pressure of < 90 mm Hg and ≥3 episodes hypotension per 10 hemodialy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Consistent with the findings of our study, Koziolek et al measured changes in whole body bioimpedance in a small number of patients and concluded that multifrequency BIA was not able to predict the onset of hypotension 15 . Although two other reports published recently have suggested a positive correlation between body compositions with intradialytic hypotension, these study findings were limited to only pre‐dialysis, and body composition pre‐dialysis is confounded by fluid status 13,14 …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Consistent with the findings of our study, Koziolek et al measured changes in whole body bioimpedance in a small number of patients and concluded that multifrequency BIA was not able to predict the onset of hypotension 15 . Although two other reports published recently have suggested a positive correlation between body compositions with intradialytic hypotension, these study findings were limited to only pre‐dialysis, and body composition pre‐dialysis is confounded by fluid status 13,14 …”
Section: Discussionsupporting
confidence: 87%
“…We hypothesized that if there was a greater fall in ECW compared to ICW during HD, then patients would be at greater risk of intradialytic hypotension. [13][14][15] Understanding the physiology, changes in hydration status, and correlation with hypotension during HD session itself using BIA may provide insight on advancement in monitoring and preventive tools to reduce the risk of intradialytic hypotension. We, therefore, studied changes in hydration status and relative change in ECW to ICW (EIR) in different body segments in high-risk ESRD patients during HD sessions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMI is linked to IDWG and therefore UFR, but patients with higher BMI appear to be able to better tolerate larger UFV and fluid depletion. 34 Two studies showing that BMI had no association with IDH, whereas increased fat and reduced lean tissue were associated with IDH, 35 , 36 may point to the problems in BMI as a surrogate for body composition. IDWG is independently linked to IDH 37 and mortality 38 ; however, IDWG is also strongly linked to nutrition, and this has been shown to impact on the relationship between IDWG and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac hemodynamic instability during hemodialytic procedure were evaluated by IDH, and myocardial ischemia. A decrease in SBP ≥ 20 mmHg or mean arterial pressure (MAP) ≥ 10 mmHg was required to quantify hypotension and ≥3 episodes hypotension per 10 hemodialysis treatments were required to diagnose IDH 29 . The rate-pressure product (RPP) was calculated as SBP multiplied by HR and the change in RPP as the percentage difference between the maximum value and the minimum value during dialysis session 13 .…”
Section: Study Protocolmentioning
confidence: 99%